2000
DOI: 10.1046/j.1472-765x.2000.00747.x
|View full text |Cite
|
Sign up to set email alerts
|

Survey for psychrotrophic bacterial pathogens in minimally processed lettuce

Abstract: A total of 120 minimally processed, cut and packaged lettuce samples were purchased from retail supermarkets or provided by a salad production facility over an 8‐month period. The samples were tested for total aerobic plate counts and for the presence of potentially pathogenic species belonging to the genera of Listeria, Aeromonas and Yersinia. The aerobic plate counts ranged from 103 to 109 colony forming units (cfu) g−1. Most samples (76%) contained between 105 and 107 cfu g−1 total aerobic bacteria. Listeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
31
1
5

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(41 citation statements)
references
References 19 publications
2
31
1
5
Order By: Relevance
“…Vegetables have been reported to be contaminated by L. monocytogenes (De Simó n, Tarragó, & Ferrer, 1992;Francis, Thomas, & O'Beirne, 1999;Szabo, Scurrah, & Burrows, 2000). Unfortunately, it has been demonstrated that industrial process rendering RTE vegetables like sanitized washing, do not guarantee the total elimination of the pathogen when present (Nguyen-The & Carlin, 1994;Szabo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Vegetables have been reported to be contaminated by L. monocytogenes (De Simó n, Tarragó, & Ferrer, 1992;Francis, Thomas, & O'Beirne, 1999;Szabo, Scurrah, & Burrows, 2000). Unfortunately, it has been demonstrated that industrial process rendering RTE vegetables like sanitized washing, do not guarantee the total elimination of the pathogen when present (Nguyen-The & Carlin, 1994;Szabo et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…For that reason, some Aeromonas species have been classified as emerging pathogens (Szabo et al 2000, Edberg et al 2007.…”
mentioning
confidence: 99%
“…Utilizou-se o ágar MRS com 0,2 e 20% (p/v) do produto, mas pode proporcionar oportunidade para o crescimento de espécies psicrotróficas anaeróbias facultativas (FRANCIS;O'BEIRNE, 2001;THOMAS;O'BEIRNE, 2000). Considerando que a maioria desses alimentos é consumida sem nenhum tratamento térmico, uma das principais preocupações é com relação a bactérias patogênicas capazes de crescerem em temperatura de refrigeração (FARBER, 1991;SCHUENZEL;HARRISON, 2002;SZABO;SCURRAHAND;BURROWS, 2000). Dentre os patógenos que podem ser encontrados em produtos vegetais frescos destacam-se Aeromonas hydrophila, Clostridium botulinum, Listeria monocytogenes, Yersinia enterocolitica, Salmonella spp., Escherichia coli O157:H7 e Campylobacter jejuni (DHOKANE et al, 2006;SCHUENZEL;HARRISON, 2002;SZABO;SCURRAHAND;BURROWS;.…”
Section: Seleção Da Bactéria Lática a Ser Inoculada Na Couve Minimameunclassified